Smart solar-regulating phase-change thermal storage window - Michael Kerenza Gouw (Nanyang Technological University, 2021)
Phase change material (PCM) is commonly researched and used as thermal energy storage by utilizing its latent heat. Gelatin is an example of PCM that has good transparency and favorable transition temperature. Hydroxypropyl cellulose (HPC) is a promising thermochromic material which shows attractive solar regulating properties. Combining gelatin’s property as PCM and HPC’s property as thermochromic material can produce a superior material for smart solar-regulating phase-change thermal storage window application.